Pyogenic granuloma associated with mandibular odontoma. - Karla Ocampo; Liliana Díaz; José Barrera (Universidad de Concepción., 2014)
Background: pyogenic granuloma is a kind of inflammatory hyperplasia of multifactorial origin, which is usually related to trauma or constant irritation, drug use, hormonal factors, among others. Meanwhile the odontoma is a benign tumor odontogenic composed of epithelial and mesenchymal cells, their development is usually associated with trauma, infections, inherited disorders or hyperactivity odontoblast. Objectives: The objective is to present the clinical case of a patient that presented a case of pyogenic granuloma related to the presence of a mandibular odontoma, and therapeutic management and postoperative results. Case report: The case shows a female patient of 32 years old with a history of multinodular goiter and hypothyroidism, developing a mandibular odontoma of the left side associated with pyogenic granuloma in the same area, which was treated with surgical excision and reconstructed affected tissues with lyophilized bone and collagen membrane. Favorable outcome after surgery without evidence of recurrence, with proper osseointegration of alloplastic materials and soft tissues. Conclusions: The irritant effect of the presence of a tumor (odontoma) in developing confirmed pyogenic granuloma.